Evaluation of Some Cardiac Functions among Children with Vitamin D Deficiency Rickets - Kotb A Metwalley; Duaa M Raafat; Asmaa F Hassan (Annals of Circulation - Peertechz Publications, 2016)
Vitamin D deficiency rickets (VDDR) is commonly recognised disease in Egypt. The most striking  biochemical fi nding in this illness is hypocalcaemia which may affect ventricular contraction. This study was a prospective hospital based study aiming to evaluate some cardiac functions among children with VDDR by Echocardiography. Patients and Methods: Patients: The included 100 patients (Group 1) with VDDR in addition to control group (Group 2) which included 50 healthy children. Methods: all cases were subjected to a thorough history, full clinical examinations and investigations which include: serum calcium, phosphorus, alkaline phosphatase, 25(OH) vitamin D, parthhormone, chest x ray, electrocardiogram and echocardiography to measure [left ventricular functions systolic function which include( ejection fraction% (EF%), fraction shortening% (FS%) left ventricular end diastolic diameter(LVEDD) and left ventricular end systolic diameter (LVESD)] . Results: EF%&FS% were signifi cantly lower while LVEDD & LVESD were signifi cantly higher among studied VDDR cases (Group 1) when compared with control (Group 2). These echocardiographic parameters were improved with treatment with vitamin D and calcium. Conclusions: children with VDDR have a signifi cant impairment in left ventricle systolic functions which improved with appropriate treatment.